On the distribution parameter of null scrolls in the Minkowski 3-space ?3 1 - Ergüt, Mahmut; Balgetir, Handan; Ö?renmiş, Alper Osman (Walter de Gruyter GmbH, 2006)
In this paper, the distribution parameter of a null scroll which is obtained by a null straight line moving along a null curve and some theorems related to the distribution parameter are given in the 3-dimensional Minkowski space ?3 1. © 2006 Warsaw University. All rights reserved.
Keywords: Distribution parameter; Null curve; Null scroll